The perception of voice onset time: A cross language study of American English and Danish - Christensen, Jens B. (Annual Report of the Institute of Phonetics University of Copenhagen, 1984)
This paper examines the relationship between the production and perception of the voicing distinction for American English and Danish stop consonants in initial position. In a comparison of the production of /p/ and /k/ for the two languages the Danish stops were found to have longer aspiration. It was therefore hypothesized that perceptually, Danish listeners would have a later cross-over point than American listeners. This was tested in a labelling experiment, using computer-edited, naturally produced stimuli. The aspiration was shortened from right to left to produce a series of stimuli ranging in VOT from +10 to +70 msec of the syllables pi, pu, ki, and ku. The listening tests showed a statistically significant difference in the expected direction for the labial stimuli but not for the velars. This may be due to the stimulus range which proved to be less appropriate for Danish listeners than for American listeners.